Reducing Stability of Support Structure for a Target Does Not Alter Reach Kinematics among Younger Adults - Cooper, S. A.; Doan, J. B.; Pellis, S. M.; Whishaw, I. Q.; Brown, L. A. (Perceptual and motor skills, 2005)
Investigation into the reach-to-grasp movement has indicated that this movement sequence is composed of two distinct movement components, independently influenced by the characteristics of the target. It remains undetermined whether properties other than those conveyed by the target also influence the strategy used to complete the task successfully. Here, we explored whether characteristics of the support structure influence reaching kinematics among younger adults. The purpose of the study was to assess whether support structure stability affected movement kinematics of the transport phase. Subjects were required to reach for a full glass of water on a stable or an unstable support structure. Kinematic measures of interest included transport time, peak transport velocity, peak transport acceleration, and timing of kinematic peaks. Analysis showed that reducing the stability of the support structure did not significantly affect any of the measures of interest. The results imply that stability of support structure does not influence transport kinematics among younger adults.